The Effect of Age on Clinical and Laboratory Parameters in Reproductive Age Women with Endometrial Polyps - Aytekin Tokmak; Ebru Ersoy; Ali Özgür Ersoy; Esra Yaşar Çelik; Ali İrfan Güzel; Mustafa Uğur (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To compare clinical and laboratory parameters in middle and advanced reproductive age women with endometrial polyps. STUDY DESIGN: We designed a retrospective study among reproductive age women who were managed at our clinic with the diagnosis of endometrial polyps. Thirty seven women older than 40 years of age (study group), and 113 women younger than 40 years (control group) were compared in terms of various clinical and laboratory parameters including age, body mass index (BMI), gravidity, parity, abortion, basal hormone levels, tumor markers, complete blood count values, smoking status, presence of polycystic ovary syndrome (PCOS), infertility status, co-morbidities, and number and size of endometrial polyps. RESULTS: The mean age of patients in the study and control groups were 45.2±3.5 and 30.6±4.9 years, respectively (p<0.001). The median BMI, gravidity, parity and abortion were significantly higher in study group (p<0.05). Infertility was more common in control group (65.5% vs. 10.8%; p<0.001). Fasting plasma glucose, basal FSH (follicle stimulating hormone) and estradiol (E2) levels were higher in study group than control group (p<0.05). Mean tumor marker levels were similar in both groups. Complete blood count values, smoking status, presence of PCOS, and number and size of polyps did not differ significantly between the two groups. The most common location of endometrial polyps within the uterine cavity was the posterior wall. There was no correlation between number and size of polyps and basal hormone levels (p>0.05). CONCLUSION: According to this study, 40 years of age and older women with endometrial polyps were more obese and had higher basal FSH and E2 levels. Obesity and increased estrogen levels may be contributing risk factors for developing endometrial polyps in women over 40 years of age.